Introduction to active power filters - Khadem, Shafiuzzaman Khan; Basu, M.; Komurcugil, Hasan (Elsevier, 2025)
The chapter provides a foundational overview of the critical role that Active Power Filters (APFs) play in enhancing power quality and grid stability within modern smart grid networks. As global energy systems transition toward decarbonization and increased integration of Variable Renewable Energy (VRE) sources such as wind and solar, challenges related to harmonics, voltage fluctuations, and reactive power imbalances become more prevalent. This chapter outlines the limitations of traditional grid infrastructure and introduces APFs as dynamic, real-time solutions for maintaining power quality in the face of these challenges. It details various APF configurations—shunt, series, and hybrid—and highlights their evolving capabilities through advances in digital control, artificial intelligence, and integration with renewable and storage systems. Furthermore, the chapter sets the stage for the rest of the book by presenting the structure of subsequent chapters, which delve into APF design, control strategies, topologies, and their applications across distributed generation systems, microgrids, and electric vehicle integration. The following chapters also emphasize the importance of APFs in ensuring the reliability, efficiency, and stability of future decarbonized smart grid networks. © 2026 Elsevier Inc. All rights reserved.
Keywords: Active power filters (APFs); Grid stability; Power quality; Renewable energy integration; Smart grid